Language proficiency, a necessity for acquiring knowledge, doing research and getting a job - BOUSSEBAT , Omar (Journal of Human Sciences, 2021)
In this contribution, we talk about of importance of languages proficiency in the appropriation of knowledge, research or the quest for a job. To get an idea of the linguistic level of our informants, first-year undergraduate students, enrolled in the department of Letters and French Language at the university of Mentouri brothers, Constantine 1, and in order to discover their short comings, we relied on a questionnaire which includes closed and open questions and on a corpus which includes audio recordings and written productions. The qualitative analysis of the questionnaire and of the corpus revealed that our respondents come up against articulatory, orthographic, morphosyntactic, interference and punctuation difficulties.